Pengaruh Mendengarkan Musik Terhadap Kondisi Rilaksasi - Djohan, Djohan; Tyasrinestu, Fortunata; Sualang, Lady Angela Exlesia (Institut Seni Indonesia Yogyakarta, 2022)
ABSTRACT The Impact of Listening to Music on Relaxation Condition. This study was conducted to identify the effectiveness of passively using instrumental music in stimulating subjects to reach relaxation. Music has been used for centuries in association with trance condition. Currently, the use has been developing, including in the realm of hypnosis or